2022
DOI: 10.3390/ijms23062956
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruptors and Endometrial Cancer: Molecular Mechanisms of Action and Clinical Implications, a Systematic Review

Abstract: It has been widely demonstrated that endocrine disruptors play a central role in various physiopathological processes of human health. In the literature, various carcinogenic processes have been associated with endocrine disruptors. A review of the molecular mechanisms underlying the interaction between endocrine disruptors and the endometrial cancer has been poorly developed. A systematic review was performed using PubMed®/MEDLINE. A total of 25 in vivo and in vitro works were selected. Numerous endocrine dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Endometriosis is a disease in which tissue similar to the lining of the uterus (the endometrium) grows outside of the uterus [ 7 ]. Multiple studies have reported the negative effects of a PE-rich diet on the risk and progression of endometriosis [ 13 , 19 , 20 , 21 , 34 , 41 , 53 , 59 ]; additionally, an epidemiological study reported by Messina et al found that the incidence of endometriosis was higher in Asian women than in Caucasian women, which may be attributed to their soy-rich diet [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometriosis is a disease in which tissue similar to the lining of the uterus (the endometrium) grows outside of the uterus [ 7 ]. Multiple studies have reported the negative effects of a PE-rich diet on the risk and progression of endometriosis [ 13 , 19 , 20 , 21 , 34 , 41 , 53 , 59 ]; additionally, an epidemiological study reported by Messina et al found that the incidence of endometriosis was higher in Asian women than in Caucasian women, which may be attributed to their soy-rich diet [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic use of many N-EDCs, combined with their toxicological effects (duplex effects), often results in controversial and confusing information. Few clinical or epidemiological results are available from humans, while a slightly higher number of toxicological findings are based on in vitro studies [ 8 , 19 , 20 , 21 ] and rodent [ 15 , 22 , 23 ] models. It is important to note that a substance may be an EDC for one species and not for another [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies concentrated on Chinese people and established a native cohort risk model. What's more, the molecular mechanisms underlying the development of EC have not yet been fully characterized and consequently are poorly understood 20 . The clinical heterogeneity of patients with EC probably re ects variation at the molecular level 21 ; thus, the prognostic mechanisms of EC likely vary as well.…”
Section: Discussionmentioning
confidence: 99%
“…(19) Dehydrate with alcohol and clear with xylene. (20) Use neutral gum for sealing the sections. ( 21) Read the sections.…”
Section: Immunohistochemical Assaysmentioning
confidence: 99%
“…There are a large number of both exogenous and endogenous risk factors for the occurrence of cancer, which are almost impossible to foresee. According to the literature [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and WHO [ 46 , 47 ], among the main risk factors for the occurrence of cancer (including cervical and endometrial cancer) are tobacco smoking, alcohol consumption, human papillomaviruses, unbalanced nutrition, physical inactivity, alimentary obesity, hereditary predisposition, chemical (polycyclic aromatic hydrocarbons, dioxins, pesticides, aflatoxins, arsenic, formaldehyde, nickel, asbestos, cadmium, and many others), physical (ionizing and ultraviolet radiation), and biological (infections caused by viruses, bacteria, or parasites) environmental carcinogens.…”
Section: Discussionmentioning
confidence: 99%